Effect of Different Anaesthetics on Hematology and Blood Biochemistry of Labeo rohita - Habib, Syed Sikandar; Naz, Saira; Batool, Aima Iram; Rehman, Fayyaz Ur; Ullah, Mujeeb; Kesbic, Osman Sabri; Maricchiolo, Giulia; Fazio, Francesco (Central Fisheries Research Institute (SUMAE), 2023)
The current study aims to determine the effect of four different anesthetics such as MS-222 (100 mg/L), tobacco extract (50 mg/L), propiscin (1.0 ml/L) and clove oil (40 mg/L) on the hematology and blood biochemical parameters of Labeo rohita. Blood was sampled 10 minutes after the anesthesia was administered and again after 24 hours. Except for the clove oil 24h measurements, there was a significant difference in the number of blood cells in all anesthetic applications (P<0.05). Hemoglobin and hematocrit values were not altered after 24 hours of treatment with clove oil and propiscin. MCV, MCH and MCHC values were not significantly affected in any application except clove oil 24h. Biochemical parameters, including total protein and glucose level, significantly changed (P<0.05) in propiscin and clove oil group. Enzymatic activities such as ALT changed significantly with MS-222, and AST values were nonsignificant (P>0.05) with tobacco, Change has been detected in ALP with MS-222 and tobacco calcium and magnesium showed non-significant differences with anesthetics. Overall all the parameters were affected by anesthetics used in the current research, however, it was established that 24 hours following the administration of clove oil, the discrepancies in blood values had vanished to a great extent.
Keywords: Clove oil, Labeo rohita, MS-222, Propiscin, Tobacco extract; 3. Good health